The effect of spin-orbit coupling on magnetoresistance in nonmagnetic organic semiconductors - 赵俊卿 丁猛 张天佑 张宁玉 庞岩涛 季燕菊 陈莹 王凤翔 付刚 (Chinese physics B, 2012)
We investigated the effect of spin-orbit coupling on magnetoresistance in nonmagnetic organic semiconductors.A Lorentz-type magnetoresistance is obtained from spin-orbit coupling-dependent spin precession under the condition of a space-charge-limited current.The magnetoresistance depends on the initial spin orientation of the electron with respect to the hole in electron-hole pairs,and the increasing spin-orbit coupling slows down the change in magnetoresistance with magnetic field.The field dependence,the sign and the saturation value of the magnetoresistance are composite effects of recombination and dissociation rate constants of singlet and triplet electron-hole pairs.The simulated magnetoresistance shows good consistency with the experimental results.